2021
DOI: 10.46303/jcsr.2021.6
|View full text |Cite
|
Sign up to set email alerts
|

Towards Socially Just Literacy Teaching in Virtual Spaces

Abstract: This study inquires into preservice teachers’ teaching experiences within a virtual tutoring field experience in a literacy methods course. Our work is situated against the greater institutional and social-political context of a competency-based model in education and the Covid-19 pandemic that led to a shift to online instruction. From a social justice lens, we approach the research questions: What are undergraduate preservice teachers’ literacy teaching experiences in a newly-transformed-to-online literacy m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The building of empathy is important because as Williams et al (2021) observed, there are inequitable access to technology and limited digital efficacy issues experienced by learners in online classrooms. One of the challenges for teacher education is to determine ways in which the preservice teachers can fulfil the work-integrated learning requirements of the teachers' qualification when face-to-face learning is not possible (Mutton, 2020;Isidro & Teichert, 2021). Carrillo and Flores (2020) concluded that teacher education needs to adapt by developing new pedagogies in the wake of online learning.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The building of empathy is important because as Williams et al (2021) observed, there are inequitable access to technology and limited digital efficacy issues experienced by learners in online classrooms. One of the challenges for teacher education is to determine ways in which the preservice teachers can fulfil the work-integrated learning requirements of the teachers' qualification when face-to-face learning is not possible (Mutton, 2020;Isidro & Teichert, 2021). Carrillo and Flores (2020) concluded that teacher education needs to adapt by developing new pedagogies in the wake of online learning.…”
Section: Review Of Literaturementioning
confidence: 99%